Efektivitas Pasal 107 Ayat (2) Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan - Antory Royan Adyan (Law Faculty of Universitas Bandar Lampung, 2012)
One of the conducted by effort is government in lessening great street accident is strarting to be gone into effect Code Number 22 Year 2009 about Traffic and Transportation Road, where decanted some new rule in the form of regulation obliging consumer society walke to turn on the light day time to rider of wheel motor vehicle two, as which is decanted in rule of Section 107, where pursuant to result of research which is komprenhensif by police, by turning on the light day time to rider of wheel motor vehicle two making vehicle become in evidence and directly improve journey security storey;level. Besides proven by turning on the light day time earn meminimalisir accident of rider of wheel two. But go into effect rule of Section 107 not yet earned to be told to go into effectively.